Mobility of the Elderly According to Their Place of Residence and Gender and Age - Hadner, Maja (Journal for Geography, 2022)
Mobility of the Elderly According to Their Place of Residence and Gender and Age The article provides some insights into the mobility of elderly people living in different settlements, differing in gender and age. Based on the data collected by the survey, the frequencies of departures from home, the most frequently travelled distances and the common ways of overcoming distances in the elderly were determined . We compared the collected data and searched for differences in place of residence, gender and age of elderly people.